2023
DOI: 10.1002/jgh3.12886
|View full text |Cite
|
Sign up to set email alerts
|

A Malaysian consensus report on the diagnosis and treatment of Helicobacter pylori infection

Abstract: Helicobacter pylori is one of the most common chronic bacterial infections in humans and responsible for 90% of duodenal ulcers and 70-90% of gastric ulcers. Despite this, many misconceptions regarding the appropriate diagnostic method and treatment strategies still exist in the Malaysian clinical practice. Under the initiative of the steering committee, an expert panel consisting of nine key opinion leaders in the field of gastroenterology convened to develop a set of consensus statements that are relevant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…As such, in each country, their local antimicrobial resistance patterns are important in influencing the formulation of first-line treatments for H. pylori infection. Hence, knowing the resistance profile of H. pylori , especially to amoxicillin, the first-line treatment antibiotic will guide the choice of antibiotic combinations, enhancing the success rate of H. pylori eradication [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, in each country, their local antimicrobial resistance patterns are important in influencing the formulation of first-line treatments for H. pylori infection. Hence, knowing the resistance profile of H. pylori , especially to amoxicillin, the first-line treatment antibiotic will guide the choice of antibiotic combinations, enhancing the success rate of H. pylori eradication [32].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Maastricht V/ Florence Consensus Report, amoxicillin is always paired with either clarithromycin, metronidazole or levofloxacin in the standard first-line therapy [4]. In Malaysia, the combination of clarithromycin, amoxicillin and rabeprazole (proton pump inhibitor) is recommended for H. pylori eradication [5]. However, the efficacy of clarithromycin has declined due to the rising antibiotic resistance in H. pylori [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent consensus on H. pylori management in Malaysia, another inter-CLA country in the region, this regimen is still recommended as an option for first-line treatment, but the 14-day duration is emphasized as an essential point. 19 However, inter-CLA countries should have rigorous monitoring programs for clarithromycin resistance. Regarding secondline therapy, the most common regimen was PBMT (59.8%) if regimens other than PBMT had been used, while the availability of bismuth in the inter-CLA countries was 72.3%.…”
Section: Discussionmentioning
confidence: 99%
“…11,16 However, in this study, we address the inter-CLA group separately because recent real-world studies across countries in this group have shown that the eradication rate of the 14-day triple clarithromycin-based regimen remained over 90% given that the treatment duration was 14 days, and it is still recommended as a firstline regimen in recent updated national guidelines. [17][18][19] All statistical analyses were performed with SPSS 23 (SPSS Inc.).…”
Section: Methodsmentioning
confidence: 99%